UPAYA UNI EROPA DALAM PENYELESAIAN KONFLIK DI TRANSNISTRIA (2002-2010) - Muhammad Reza Satria; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This resesearch describes the separatism conflict between Moldova and Transnistria which European Union since 2002 came and use their power to reduce and minimalize Transnistria conflict since 1992. EU main objectives are to provide greater understanding between Moldova and Transnistria to minimalize their ego with settlement and MoU which the result is a win win solution to Moldova and transnistria.This research uses strategic theory. Qualitative method and library research are applied in this research. The sources of information that used in this research are taken from book, journal, news, and internet.This research explains the efforts of European Union as international organization to reduce and minimalize conflict in Molodva, especially Transnistria. There are some hypothesis’ to describe the efforts which implemented by EU. This research also describes the progress from European Union to minimalize the conflict since intervention from 2002. The results of this research show that UNODC’s efforts can reduce the separatism conflict in Moldova.Keywords: European Union, Moldova, Transnistria, Conflict, Separatism